Impact of Coaching on Employee Productivity - Irmayani, Okta (Westscience Press, 2025)
Dynamic changes in the workplace require organizations to adopt effective strategies to improve the quality and productivity of their workforce. One increasingly popular approach is coaching, a personal development process aimed at developing individual skills and helping them face work challenges. This study examines the effect of coaching on employee performance and the factors that influence their success within the organization. The method used is bibliometrics, analyzing academic articles related to coaching published in the past five years. The study results indicate that coaching has a positive impact on employee performance, both directly and through improved work attitudes such as motivation, engagement, and responsibility. The success of coaching is influenced by the method applied, the readiness of the individual being coached, the competence of the coach, and organizational support. This study provides academic contributions to the field of human resource development and practical recommendations for organizations seeking to maximize employee potential through targeted and personalized coaching.